The ethnobotany of Ngusaba ceremonial plant utilization by Tenganan Pegringsingan community in Karangasem, Bali, Indonesia - DEWA AYU SRI RATNANI; I Ketut Junitha; Eniek Kriswiyanti; I Nyoman Dhana (Society for Indonesian Biodiversity, 2021)
Abstract. Ratnani DA, Junitha IK, Kriswiyanti E, Dhana IN. 2021. The ethnobotany of Ngusaba ceremonial plant utilization by Tenganan Pegringsingan community in Karangasem, Bali, Indonesia. Biodiversitas 22: 2078-2087. Tenganan Pegringsingan is an ancient village in Bali, Indonesia, which often performs several ceremonies with high intensity. One of them is the Ngusaba ceremony, where many plants are utilized both in species and quantity. Hence, this study aimed to identify the species, family, local names, sources, and parts of plants, used for Ngusaba ceremonies by the Tenganan Pegringsingan community including the Index of Cultural Significance (ICS). Data analysis was qualitative and quantitative. Furthermore, the qualitative method was used to obtain data on the plants’ local names, while snowball sampling was applied to select key informants through in-depth interviews and moderate participation. The results showed that the 130 species distributed in 56 families mostly belonging to the purchased source (34.61%). The Poaceae is the largest family, while the most widely used part of the plant is the leaf. Based on the ICS analysis results, a range of 2-114 values was obtained. The highest value is Base (Piper betle L.) and kangkung (Ipomoea batatas L.) as lowest.